In vitro and in vivo anti-malignant melanoma activity of Alocasia cucullata via modulation of the phosphatase and tensin homolog/phosphoinositide 3-kinase/AKT pathway. (1st March 2018) - Fang, Miao; Zhu, Daoqi; Luo, Chaohua; Li, Chan; Zhu, Chen; Ou, Jinying; Li, Hancheng; Zhou, Yuting; Huo, Chuying; Liu, Wei; Peng, Jiangli; Peng, Qiuxian; et al.
Abstract: Alocasia cucullata, a Chinese herb, has been used as an anticancer treatment in southern China. Phosphatase and tensin (PTEN), is a tumor suppressor gene and the loss of PTEN expression may activate the phosphoinositide-3-kinase (PI3K)/AKT signaling pathway which play a key role in tumors formation and progression. In this study, we evaluated the anti-melanoma effect and the underlying mechanism of 50% ethanolic extract of A. cucullata (EAC) in vitro and in vivo. Using MTT, wound healing, and transwell assays, we found that EAC suppressed the proliferation, migration, and invasion of melanoma cells (B16-F10, A375 and A2058) in a dose-dependent manner. We also found that EAC suppresses B16-F10 tumor growth in a xenografted mouse model. Western blot analysis revealed that the expression level of PTEN was up-regulated, and phosphorylation of PI3K and AKT reduced in B16-F10 cells and tumor tissues after EAC treatment. No significant differences were observed in PI3K and AKT expression. Moreover, immunohistochemistry showed that the number of PTEN-positive cells in tumor tissues increased and that of p-AKT-positive cells decreased with EAC treatment, corroborating the western blot results. Our data reveal that EAC can inhibit malignant melanoma in vitro and in vivo and suggest that its anti-tumor effect is associated with modulation of the PTEN/ PI3K/AKT signaling pathway. In summary, our findings highlight a promising herbal remedy for the treatment of malignant melanoma, which warrants further study. Graphical abstract: